BANK MERGER BENEFITS: A STUDY FROM STAKEHOLDERS' PERSPECTIVE (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
The study aims to assess the benefits of bank  mergers from the point of view of bankers and  researchers. As merger of banks has been taking  place in India in regular intervals, extensive  research is conducted in the study to analyse  the benefits of merger. Primary and categorical  data has been used for the study. A scheduled  questionnaire is prepared for data collection.  A total of 217 responses are processed for the  study purpose. Six factors are extracted from  exploratory factor analysis. It is found that bank  merger has financial benefit and market benefit.  The present study will help bankers to design a  comprehensive merger strategy.
Keywords: Bank merger; Merger benefit; Social benefit; Economic benefit JEL Classification; G21; E58; L60; M14